Innovations for smoke management in passenger trains. (March 2020) - Lázaro, Mariano; Lázaro, David; Cortabarria, Edurne; Alvear, Daniel
Spanish manufacturer Construcciones y Auxiliar de Ferrocarriles developed an innovative alternative for compartmentation, based on a smoke extraction system, to guarantee safe conditions during evacuation processes in a passenger unit. To demonstrate its performance in a train unit, a real-scale experimental programme, supported by the application of fire computer modelling, was applied in a new Construcciones y Auxiliar de Ferrocarriles' rolling stock. The new smoke exhaust system aims to extract the smoke generated during a fire in the passenger area by exhaust fans of the heating, ventilation, and air conditioning system, allowing the ingress of fresh exterior air in the lower part of the rear ends of the car. These key elements create an air flow that evacuates the smoke to prevent people from being exposed to it. Full-scale fire tests were developed in the train unit following the Australian standard AS 4391-1999. A fire of 140 kW was used, and the smoke was generated by a clean smoke machine. Measurement points included six thermocouple trees, 10 gas flow velocity probes and two GoPro HD video cameras (for the estimation of the visibility). The system performance was successful with the tenability criteria, since the value of visibility at the non-fire car was greater than 30 m and the temperature was lower than 30°C during all the tests at a height of 1.7 m above the floor. Experimental results were used to validate the computational model. The computational model results show a good accuracy compared with the tests.